Gene Transfer and Expression Protocols - Murray, Edward J. (Methods in Molecular Biology,, 1991)
Biology is the study of living things. The classical approach might be described as holistic and descriptive, whereas the modern molecular - proach aims to be investigative, reductionist, and mechanistic . Genes contain all the information for the structure of all living things ; thus, the understanding of how genes are regulated is an important step toward understanding the nature of living things. The study of gene regulation has been made more tractable by the design of simple expe- mental models in which a single gene can be isolated from the milieu of the organism. The new science of molecular biology has introduced techniques that permit the design of such experimental models. In - sence, the genome of the organism is dissected in such a manner that specific genes may now be introduced into an appropriate cell line . Subsequent analysis of the proteins expressed from the genes under study results in the identification of the regulatory DNA sequences .